2004
DOI: 10.1111/j.1468-1331.2004.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress lactate in mitochondrial myopathy under constant, unadjusted workload

Abstract: As it is under debate if determination of lactate during cycle ergometry (lactate stress testing, LST) under a continuous, unadjusted, low workload is a valuable diagnostic tool for mitochondrial myopathy (MMP), the present study aimed to investigate how sensitive the LST is in a large cohort of patients with indications for MMP (MMP patients). Serum lactate was determined once before, three times during, and once after a 15-min, constant 30 W-workload on a bicycle ergometer in 115 healthy controls, 166 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…29 It could then be argued that the prevalent atrophy of slow-twitch muscle fibers in DM1 could represent one of the possible mechanism implied in the altered oxidative capacity evidenced in such patients, thus providing basis for the abnormal lactate levels assessed performing our aerobic protocol. So, as far as lactate determination during cycle or treadmill ergometry is used for diagnostic purpose in mitochondrial myopathies, 30 this submaximal exercise could be a tolerable and safety method to assess aerobic capacity in this kind of patients. The interest of our study consists of the fact that our protocol is a safe, non exhaustive and easy reproducible method to be performed in such patients, who may frequently present early structural and functional myocardial abnormalities, strongly associated with cardiac conduction alterations.…”
Section: Discussionmentioning
confidence: 99%
“…29 It could then be argued that the prevalent atrophy of slow-twitch muscle fibers in DM1 could represent one of the possible mechanism implied in the altered oxidative capacity evidenced in such patients, thus providing basis for the abnormal lactate levels assessed performing our aerobic protocol. So, as far as lactate determination during cycle or treadmill ergometry is used for diagnostic purpose in mitochondrial myopathies, 30 this submaximal exercise could be a tolerable and safety method to assess aerobic capacity in this kind of patients. The interest of our study consists of the fact that our protocol is a safe, non exhaustive and easy reproducible method to be performed in such patients, who may frequently present early structural and functional myocardial abnormalities, strongly associated with cardiac conduction alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that a constant workload cycle test below anaerobic threshold is a more sensitive and specific diagnostic test for MM, respect to an incremental cycle test to exhaustion, even though, in their study, resting lactate seemed a more sensitive marker of MM than the exercise tests. On the contrary, Finsterer et al [71] applied a cycle ergometry test with a continuous, unadjusted, low workload protocol, and they concluded that the exercise test had a higher sensitivity than resting lactate values.…”
Section: Aerobic Exercise Testmentioning
confidence: 99%
“…3 Increased lactate production and early anaerobic threshold in a patient with mitochondrial myopathy performing an incremental exercise cycle ergometer test desaturation and lactate increase in patients with MM [74]. Moreover, a significant correlation between the aerobic test response and the degree of muscle involvement or histopathological findings has been described [71,72]. It has to be taken into account, however, that a normal aerobic exercise test does not exclude a diagnosis of MM.…”
Section: Aerobic Exercise Testmentioning
confidence: 99%
“…Creatine-kinase was slightly elevated (267 U/l, n: <170 U/l), resting lactate was normal, but lactate stress testing was abnormal with a maximal increase to 5.2 mmol/l (n: <2.1 mmol/l) [2]. Nerve conduction studies of various motor nerves revealed reduced nerve conduction velocity of the left peroneal nerve exclusively.…”
Section: Introductionmentioning
confidence: 97%